The Plant Growth-Promoting Bacterium Bacillus cereus LpBc-47 Can Alleviate the Damage of Saline–Alkali Stress to Lilium pumilum - Miaoxin Shi; Lingshu Zhang; Hao Sun; Shangwei Ji; Huitao Cui; Wenhao Wan; Xingyu Liu; Ao Tian; Wei Yang; Xinran Wang; Fengshan Yang; Shumei Jin (Microorganisms, 2025)
Soil salinization severely impacts plant cultivation. Lilium pumilum (L. pumilum) exhibits tolerance to saline–alkali stresses. One Bacillus cereus strain, LpBc-47, possesses the ability of growth promotion and saline–alkali tolerance. The microbial diversity of L. pumilum was assessed through metagenomic sequencing. LpBC-47 obtained from L. pumilum was subjected to physiological and biochemical analyses and whole-genome sequencing. The effects of endophytic bacteria on plants were evaluated by measuring growth parameters, physiological indices, antioxidant enzyme activities, and ROS content. Microbial diversity analysis revealed that the abundance of endophytic bacteria in L. pumilum decreased under saline–alkali conditions, whereas the abundance of Bacillus cereus increased. Physiological and biochemical analysis showed that LpBC-47 has the characteristics of promoting growth and reducing plant damage caused by salt–alkali stress, such as phosphorus solubilization, nitrogen fixation, siderophore production, IAA, and ACC deaminase synthesis. Genomic analysis revealed that LpBC-47 contains growth-associated and stress-alleviation genes. GFP indicated the colonization of LpBc-47 in the roots and bulbs of L. pumilum. The LpBc-47 inoculant plant increased leaf length and dry weight, elevated proline and chlorophyll levels, enhanced antioxidant enzyme activity, and reduced oxidative damage. This study highlights the potential of LpBc-47 for improving plant growth under saline–alkali conditions.